(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The blend of poly(lactic acid) (PLA) and poly(butylene succinate) (PBS) were prepared and extruded with various compositions and their molded properties were examined. Thermogravimetric analysis showed that thermal stability of the blends was higher than that of pure PLA and the weight loss of PLA/PBS (40/60 wt%) was lower than neat polymers. Differential scanning calorimetry thermograms of blends indicated that the thermal properties of PLA did not change noticeably when blended with PBS. The tensile strength and modulus of blends decreased with the increasing PBS content. But impact strength has improved about two times compared to pure PLA. Rheological results revealed that the addition of 10% and 20% of PBS increased the storage modulus, loss modulus and viscosity of the blend at nearly all frequencies, and decreased viscosity with increasing shear stress. Dynamic mechanical properties results showed the lowering of storage modulus of all blended PLA which indicated the increase of molecular mobility by adding PBS due to lower glass transition.